Small but diverse: larval trematode communities in the small freshwater planorbids Gyraulus albus and Segmentina nitida (Gastropoda: Pulmonata) from the Ruhr River, Germany - Vyhlídalová, Tereza (Jihočeská univerzita, 2020)
This study reveals the importance of small planorbid snails, in particular Gyraulus albus, as first intermediate hosts for a species-rich trematode fauna in European freshwater systems, and highlights the parasite contribution to the ecosystem biodiversity.
Small but diverse: larval trematode communities in the small freshwater planorbids Gyraulus albus and Segmentina nitida (Gastropoda: Pulmonata) from the Ruhr River, Germany
Keywords: Planorbidae; Digenea; Parasite diversity; Community composition; Reservoir; Europe; Planorbidae; Digenea; Parasite diversity; Community composition; Reservoir; Europe